Hubungan pola nutrisi dengan penyembuhan luka perineum pada ibu nifas hari ke-7 - Fitri Wijayanti; Hesty Widyasih; Heni Puji Wahyuningsih (Jurnal Kesehatan Ibu dan Anak, 2013)
The incidence of infection resulted from perineum rupture remained high, involving perineum wounds that had not closed completely in the seventh day of the postpartum, reddish serous fluid came out. This was caused by lack of treatment and the need for nutritional pattern which might affect the wound healing process. Nutrition is basic needs for puerperal women which will affect their health, their energy recovery their perineum wound healing, and the production of breast milk (ASI) for babies. Purpose to examine the relationship between nutritional pattern and perineum wound healing of puerperal women in the 7th day. Method: This research employed observational methods using cross-sectional approaches. This research was done in the Regional General Hospital of (RSUD) Sleman on 8-22 December 2012. The sample of the research was collected through purposive sampling techniques consisting of 30 respondents. The research instrument was food recall analyzed trough Kendall-tau. Finding: Nutritional pattern prevalence of puerperal women in the 7th day with perineum wounds of degree ll recovered in the 7th day in the Regional General (81.8%). Puerporal women in the Regional General whose perineum wounds did not recovered in the 7th day (27.7%). The result of Kendall-tau test concerning the value of p 0.019 < 0.05. Conclusion: There is a relationship between nutritional pattern and perineum wound healing of puerperal women in the 7th day in the Regional General Hospital of (RSUD) Sleman in 2012.